ANALISIS KEBUTUHAN DALAM PENGEMBANGAN MODUL DIGITAL IPAS BERBASIS ECOLITERACY DI SEKOLAH DASAR - Ramadhani, Tri Anisa; Saputra, Erwin Rahayu; Mohamad Setiadi, Pidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to identify the needs and analyze the problems of developing digital modules for science subjects based on ecoliteracy for grade V elementary school students. The research approach uses a descriptive qualitative method. The data collection techniques used include observation activities, interviews, and documentation studies. The subjects of the study include class V teachers and 3 elementary school class V students. Data analysis includes data collection activities, data selection and presentation, as well as describe conclusions or verifying data. The results of the study show that teachers have difficulties in integrating science and social studies learning due to the lack of comprehensive availability of teaching materials. In addition, the diversity of characteristics of students' understanding related to ecoliteracy can be prepared with teaching materials that can facilitate students' understanding of ecoliteracy. With the existence of learning achievement documents, the flow of learning objectives, teaching modules, and science science subject books can be used as a reference in the process of preparing teaching materials for learning modules. In line with technological developments, today's teaching materials can be electronic or digital-based. Thus, this study suggests the development of ecoliteracy-based digital modules to support students' understanding in learning science and science.